Применение процесса частичной ортогонализации к транспортной задаче линейного программирования - Дадаян, Д. С.
In this work, useing the process of partial ortogonalization, we determine the-feasible interior point in the transportation problem. This point is a normal solution which is determined through the analitic path. In the analitic frame we determine the “ Simplex Tableau” for this point which can be considered as “ Initial Tableau” for further calculations in order to find an optimal solution.
Keywords: Математика